2013
DOI: 10.1186/1477-7819-11-262
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive jaundice due to ampullary metastasis of renal cell carcinoma

Abstract: Renal cell carcinoma is often characterized by the presence of metachronous metastases in unusual sites. The presence of isolated metastases is treated with surgical excision with good anticipated results. On the other hand, systemic chemotherapy is administered in the context of metastatic spread, usually sunitib or sorafenib. In such cases, however, the presence of symptomatic foci calls for minimal intervention.We present a case of a 77-year-old patient who presented with obstructive jaundice due to an ampu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Presence of jaundice with raised liver enzymes in the presence of a suspected malignancy needs through evaluation to rule out liver metastasis and look for causes for hepatic dysfunction. Work up includes excluding any obstructive cause for jaundice like lymph nodes or malignant mass 5 at the porta hepatis, infectious causes like viral hepatitis A, B, C, relevant drug history, alcohol consumption. Involving a hepatologist for thorough evaluation in such cases and optimizing them prior to surgery is of paramount importance.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of jaundice with raised liver enzymes in the presence of a suspected malignancy needs through evaluation to rule out liver metastasis and look for causes for hepatic dysfunction. Work up includes excluding any obstructive cause for jaundice like lymph nodes or malignant mass 5 at the porta hepatis, infectious causes like viral hepatitis A, B, C, relevant drug history, alcohol consumption. Involving a hepatologist for thorough evaluation in such cases and optimizing them prior to surgery is of paramount importance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many reported cases to date stated breast cancer, kidney cancer, or malignant melanoma as the primary lesion. [5][6][7][8][9] There is only one reported case of obstructive jaundice caused by ovarian cancer due to extramural pushing/infiltration from lymph node metastasis. 12 To the best of our knowledge, there has been no reported case of obstructive jaundice caused by direct metastasis to the duodenal major papilla.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all intrabiliary tumors that cause obstructive jaundice originate in the biliary duct, although there are reports of rare cases of biliary/papillary metastasis arising from colorectal cancer, breast cancer, lung cancer, malignant melanoma, and other malignancies. [2][3][4][5][6][7][8][9] Obstructive jaundice caused by metastatic biliary tract/papillary lesions sometimes occurs because of compression or infiltration of bile ducts due to widespread liver metastases, or in exceptional cases, because of direct metastatic involvement of the extrahepatic bile ducts and duodenal major papilla in the absence of hepatic lesions. 7,10,11 We present a case of obstructive jaundice caused by direct metastasis to the duodenal major papilla from ovarian cancer that was treated surgically 11 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…On review of literature, we found only 11 reported cases of RCC metastazing to ampulla of Vater. To our knowledge, this is the 12th case of RCC with metastasis to the ampulla ( Table 1 [ 5 - 8 , 17 - 21 ]). Of these cases, seven were males and five were females.…”
Section: Discussionmentioning
confidence: 99%